Aerobic granular sludge-derived activated carbon: mineral acid modification and superior dye adsorption capacity1. Issue 32 (10th April 2015) - Zhang, Ge; Shi, Li; Zhang, Yongfang; Wei, Dong; Yan, Tao; Wei, Qin; Du, Bin
<x xml:space="preserve">Abstract</x> A novel aerobic granular sludge-derived activated carbon (AC) was prepared by a zinc chloride activation method and further modified by mineral acid (nitric acid (NA) and sulfuric acid (SA)).